FROM NEEDS ANALYSIS TO COURSE EVALUATION: A CASE STUDY OF AN ESP COURSE - Wu, Yayin (International Journal of Research -GRANTHAALAYAH, 2023)
Needs analysis is often referred to as one of the essential parts during the period of course design. This study, choosing a skilled-centred ESP course Nuclear Science English as the research object, aims to conduct needs analysis and course evaluation. It is founded that although target needs are very clear, many students still lack motivation to learn it, for the course itself fails to satisfy learners’ subjective needs. In terms of course evaluation, this ESP course is with professional teaching materials, various teaching methodology and multidimensional evaluation system. However, it is difficult for English majors to finish the course since the course designer ignores English majors’ weak learning foundation of natural science.